Rancang Bangun Sistem Informasi E-Commerce Gerai Hastani Kabupaten Banyuwangi Berbasis Website - Cholifah, Cholifah; Baijuri, Achmad (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2024)
Banyuwangi Regency, which is known as one of the agricultural centers in East Java Province and on a national scale, has very high agricultural potential. Even though agricultural products in this region are abundant, many farmers in this area still face economic difficulties. This is due to the long marketing chain, which results in the accumulation of high profits by intermediaries. As a result, the prices received by farmers as producers and those paid by final consumers have significant differences. To overcome this problem, an effective marketing strategy is needed. The Department of Agriculture and Food has introduced the innovation "GERAI HASTANI" (Gerobakku Beautiful Agricultural Products) which aims to encourage farmers to become independent in caring for, harvesting and selling their agricultural products. Because GERAI HASTANI is only available at certain points, there are still many Banyuwangi people who cannot take advantage of it. Therefore, an online sales system is needed that allows farmers to sell their products directly and adheres to the same hygiene standards as those applied at GERAI HASTANI. This is why the e-commerce information system GERAI HASTANI in Banyuwangi Regency is important. This system will help expand the reach and accessibility of GERAI HASTANI, providing benefits to more farmers and consumers.